2019
DOI: 10.1021/acs.energyfuels.9b02013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Autoignition Characteristics of the Gasoline/Diesel/Ethanol and Gasoline/Diesel/PODE/Ethanol Fuels

Abstract: Polyoxymethylene dimethyl ethers (PODE) with high oxygen content and ethanol with high octane number are ideal additives for diesel and gasoline, respectively. Previous studies have shown that diesel/gasoline fuels and diesel/gasoline/PODE fuels can significantly reduce soot emissions. To further reduce soot emissions, ethanol was blended with these two fuels in this study and the effect of ethanol on fuel ignitability was investigated by experimental study and numerical simulation. Experiments were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In this work, two side products were observed: methanol and trioxane (TOX) [50]. The appearance of methanol can formally be explained by Equations (7) and (8). The appearance of trioxane is not delved into too deeply in this work.…”
Section: Chemical Modelmentioning
confidence: 67%
See 1 more Smart Citation
“…In this work, two side products were observed: methanol and trioxane (TOX) [50]. The appearance of methanol can formally be explained by Equations (7) and (8). The appearance of trioxane is not delved into too deeply in this work.…”
Section: Chemical Modelmentioning
confidence: 67%
“…PODE n of chain lengths n = 3-5 have suitable flash points [2] and melting points [3], which could reduce the soot and also, indirectly, NOx during the combustion process in compression ignition engines [4][5][6]. Thus, higher combustion efficiency could be achieved by blending PODE n in diesel [7,8]. Moreover, PODE n can be used as oxygenated fuels to direct oxidation fuel cells [9] and as green solvents for the chemical industry [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, P100 always had the lowest PCP, PHRR and PCT. The higher oxygen content of PODE can release a large number of active free radicals during the combustion stage thereby promotes complete combustion and heat release [30,39,40]. The fuel injection quantity was fixed at 20 mg/cycle.…”
Section: Discussion For Thermodynamic Combustion Characteristicsmentioning
confidence: 99%
“…This comparison shows that the most suitable OME n to be blended into conventional diesel are those with n = 3–5 (OME 3 , OME 4 , and OME 5 ). , A study of a mixture of OME 2–6 with a CN of 72 and its blends with diesel in a CI engine showed that better ignition, combustion, volatility, and reduced exhaust emissions can be achieved in comparison to conventional diesel fuel . The ignitability of a diesel fuel has been observed to be improved with the addition of OME 3–5 , and blending OME 3 in n -heptane/ethanol mixtures improved the combustion efficiency and reduced the pollutant emissions in a combustion vessel. , …”
Section: Introductionmentioning
confidence: 89%
“…7,27 A study of a mixture of OME 2−6 with a CN of 72 and its blends with diesel in a CI engine showed that better ignition, combustion, volatility, and reduced exhaust emissions can be achieved in comparison to conventional diesel fuel. 28 The ignitability of a diesel fuel has been observed to be improved with the addition of OME 3−5 , 29 and blending OME 3 in n-heptane/ethanol mixtures improved the combustion efficiency and reduced the pollutant emissions in a combustion vessel. 30,31 The storage stability of OME 3−5 was studied according to ASTM Standard D4625-14.…”
Section: Introductionmentioning
confidence: 99%